IFPRI key facts series: Agriculture and food safety - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
This is the first in a series of Key Facts sheets that IFPRI will be producing based on the third and fourth Integrated Household Surveys (IHS). The purpose of the series is to present data relevant to key policy issues on agriculture, food systems, and development topics in Malawi. Other Key Facts sheets will be produced in the near future.